Optimization of a microgrid operation considering operation cost, life of the batteries and uncertainty cost of eolic energy (2019)
Nowadays, autonomous systems that incorporate renewable energy sources and energy storage systems play a fundamental role as a solution to energy supply problems. These systems are a good alternative, mainly in remote areas of the electricity network such as islands. This paper analyzes the cost of battery life, operation and maintenance costs and the uncertainty costs associated with renewable energy agents for an autonomous microgrid developed on Dong-fushan Island in China, all in order to obtain the adequate parameters for the optimum operation of the same, without forgetting the characteristics of useful life in specific lead-acid batteries. It is intended, through the non-dominant algorithm of genetic classification (NSGA II), to achieve maximization of the aforementioned variables: useful life of the batteries, and the reduction of the generation cost, proposing a multi-objective optimization. In addition to the above, the costs of uncertainty associated with renewable wind energy are included.